If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3m + 8)(5m + -3) = 0 Reorder the terms: (8 + 3m)(5m + -3) = 0 Reorder the terms: (8 + 3m)(-3 + 5m) = 0 Multiply (8 + 3m) * (-3 + 5m) (8(-3 + 5m) + 3m * (-3 + 5m)) = 0 ((-3 * 8 + 5m * 8) + 3m * (-3 + 5m)) = 0 ((-24 + 40m) + 3m * (-3 + 5m)) = 0 (-24 + 40m + (-3 * 3m + 5m * 3m)) = 0 (-24 + 40m + (-9m + 15m2)) = 0 Combine like terms: 40m + -9m = 31m (-24 + 31m + 15m2) = 0 Solving -24 + 31m + 15m2 = 0 Solving for variable 'm'. Factor a trinomial. (-8 + -3m)(3 + -5m) = 0Subproblem 1
Set the factor '(-8 + -3m)' equal to zero and attempt to solve: Simplifying -8 + -3m = 0 Solving -8 + -3m = 0 Move all terms containing m to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -3m = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -3m = 0 + 8 -3m = 0 + 8 Combine like terms: 0 + 8 = 8 -3m = 8 Divide each side by '-3'. m = -2.666666667 Simplifying m = -2.666666667Subproblem 2
Set the factor '(3 + -5m)' equal to zero and attempt to solve: Simplifying 3 + -5m = 0 Solving 3 + -5m = 0 Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5m = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5m = 0 + -3 -5m = 0 + -3 Combine like terms: 0 + -3 = -3 -5m = -3 Divide each side by '-5'. m = 0.6 Simplifying m = 0.6Solution
m = {-2.666666667, 0.6}
| -8.6-3z-8.5-z=-3z+2.3 | | 2(1-x)=3(x+9) | | n+12=n*4 | | 2y+3=7y | | 5(x-7)=2(x+8)+x | | 12-2x+5=-2+(x-3) | | 4(3x-5)-x=-x+16 | | -3m+7=40 | | 3x-2=3x-5+8 | | 4w+6w= | | 3(2x-1)+x=x-3 | | x-10-2x=9 | | 0=x^2-10x+50 | | 5x+5(1-x)=x+8 | | 9x-(4x-3)=11+(2x-2) | | 2x-12=3x-16 | | -3x^3-7x^2-5x+1= | | 19(13a+20)= | | 3x^3-7x^2-5x+1= | | n^2+6n-86=5 | | 12x+3=1232342 | | u^2-8u+16=0 | | 33=-8+4(c-5) | | 35x^3-28x^2=7x | | 4x^2+48=0 | | 5y=8-9y | | 21=-9(8r-3) | | 20x^2-20x^2= | | 4z-9z=6z-3+2 | | 2x+4=2x+16 | | 8x^3+30x^2+18x= | | 4x+5=3x+4 |